Regional developments: Central Asia - Akramov, Kamiljon T.; Romashkin, Roman; Ilyasov, Jarilkasin (International Food Policy Research Institute, 2021)
Central Asia faced unprecedented challenges in 2020 as the global pandemic compounded existing problems facing the region. These included the growing effects of climate change, unstable commodity markets, and a heavy reliance on remittances and undiversified trade flows. Unlike other recent shocks, COVID-19 and the associated responses forced Central Asians to change daily practices and routines, many essential to their livelihoods, and disrupted connections at the local, regional, and global levels. The short-term response by governments helped to buffer the shock, while the agriculture sector proved fairly resilient. Recovery in the main destination countries for Central Asia’s migrant laborers has already helped restore flows of remittances. For long-term transformation of the region’s food system, however, the shock has highlighted weakness in social safety nets and digital connectivity, as well as the risk of relying heavily on remittances and a limited set of exports.